If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 + y = 0 Remove the zero: y = 0 Solving y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 0
| 5x+26=3x+60 | | 0.833+2.5x=-6.5+0.66 | | 5x-8y=64 | | 10-4z=22-6z | | 18-3t=6 | | 4(1+2a)=-6a(a-3) | | 5y-3=7y | | 7+4n=23 | | 4x-3=2x+38 | | 220+220(0.105)-220(0.1)=x | | 5+5x-6=9 | | 8xn=51 | | 2x*5=4x+13 | | 4(-3k+8)=-6k+2(5k+8) | | Ix-4I=-3 | | 3n+6=16 | | F(x)=cos(pi+x) | | 3y+2=7y+10 | | g(z)=Cos(pi+g) | | 4y+2x=13.50 | | .77=In(y) | | 46=-5(m+3)-7(m-7) | | 0.77=ln(y) | | 0.5x-4=7-x | | 7+2[a-3]=-9 | | -8a+15=-105 | | 4x+2y=13.50 | | H-(-7)=12 | | 4x+2x=13.50 | | -6(a+8)+6(1-8)=-78 | | 7x-5=5x+8 | | -7x-4-4x=9x+4x |